Analysis of impact of humidity and temperature on excimer laser ablation of polyethylene terephthalate, polymethylmethacrylate, and porcine corneal tissue - Verma, Shwetabh; Kehrer, Tobias; Hesser, Jürgen; Arba Mosquera, Samuel (Lasers in surgery and medicine, 2020)
Background and Objectives - To analyze the impact of humidity and temperature on excimer laser ablation of polyethylene terephthalate (PET), polymethylmethacrylate (PMMA) and porcine corneal tissue, and an ablation model to compensate for the temperature and humidity changes on ablation efficiency.